Assessing Indonesia’s Environmental Laws Pertaining to the Abatement of Marine Plastic Pollution: A Euphemism? - David Tan (Jurnal Media Hukum, 2022)
The predominance of irresponsible and unsustainable plastic usage in Indonesia poses an urgent and alarming danger to the ecosystem. This paper discussed the legislative and regulatory mechanism in place in Indonesia to manage marine plastic pollution, the limitations and obstacles it faces, and the possibility of remedies being implemented to resolve Indonesia's marine plastic pollution predicament. The ecological approach, sustainable development goals, human right to a healthy environment, and sociopolitical context will all be used to advise this research. The findings demonstrate both top-down and bottom-up initiatives to marine plastic pollution law and regulations are ineffectual. If not adequately regulated, the government, political, and economic structural proclivities would most likely favor economic expansion at the expense of appropriate protection of the environment. Indonesia has to consider not just more comprehensive law and regulation to handle the complex concerns of marine plastic pollution, but it also sought to acknowledge other drivers that hamper the success of efforts to conserve the marine ecosystem. As a result, it is suggested that Indonesia initially focus on short-term measures prior to progressing on to long-term remedies, with effective cohesion across all approaches and collaboration with all involved parties.